Diagnostic accuracy of isolated-check visual evoked potentials for glaucoma: a systematic review and meta-analysis - Yongran Li; Yanling Lu; Tulong Lin (BMC Ophthalmology)
Abstract Background The isolated-check visual evoked potential (ic-VEP) is an advanced electrophysiological technique that selectively evaluates the magnocellular pathway, enabling precise assessment of optic nerve damage and currently serving as a diagnostic tool for glaucoma. This meta-analysis evaluates the diagnostic performance of ic-VEP in glaucoma detection. Methods The study protocol was prospectively registered in the International Prospective Register of Systematic Reviews (PROSPERO) (Registration ID: CRD42025633065) prior to data extraction. Following PRISMA guidelines, a systematic search of PubMed, Embase, Web of Science, Scopus, Ovid Medline, and Cochrane databases was conducted from inception to January 1, 2025. Studies evaluating ic-VEP for glaucoma diagnosis were included, with confirmed cases defined by standard automated perimetry (SAP). Eligible studies underwent methodological quality was appraised using the QUADAS-2 tool and Review Manager 5.3. Meta-analysis was conducted using Meta-Disc 1.4 and Stata 13.0 based on the hierarchical summary receiver operating characteristic (HSROC) model to derive pooled sensitivity, specificity, diagnostic odds ratio (DOR), and area under the curve (AUC). Publication bias was assessed using Deek’s funnel plot asymmetry test and trim-and-fill analysis. Heterogeneity was quantified via the I2 statistic, with meta-regression identifying potential sources of variability. Results Ten studies comprising 434 patients with glaucoma and 321 healthy controls met the inclusion criteria. Pooled sensitivity and specificity for glaucoma diagnosis were 0.77 (95% CI: 0.71–0.82) and 0.93 (95% CI: 0.80–0.98), with an AUC 0.86 (95% CI: 0.83–0.89). The DOR was 44.96 (95% CI: 15.25–132.51) and the lambda value was 3.70 (95% CI: 2.73–4.66). Both Deek’s funnel plot asymmetry test (p = 0.30) and trim-and-fill analysis (imputed studies = 4) demonstrated no substantial publication bias. Meta-regression identified type of device (Neucodia vs. EvokeDx) and type of glaucoma (early POAG vs. others) as contributors to heterogeneity. Conclusions Despite limited included studies and sample sizes, ic-VEP exhibits high diagnostic accuracy for glaucoma, offering advantages such as objectivity, non-invasiveness, and operational simplicity. These findings support its integration into clinical workflows for glaucoma screening and diagnosis.